Positive Darwinian selection drives the evolution of several female reproductive proteins in mammals - Swanson, Willie J. (The National Academy of Sciences, 2001)
Rapid evolution driven by positive Darwinian selection is a recurrent theme in male reproductive protein evolution. In contrast, positive selection has never been demonstrated for female reproductive proteins. Here, we perform phylogeny-based tests on three female mammalian fertilization proteins and demonstrate positive selection promoting their divergence. Two of these female fertilization proteins, the zona pellucida glycoproteins ZP2 and ZP3, are part of the mammalian egg coat. Several sites identified in ZP3 as likely to be under positive selection are located in a region previously demonstrated to be involved in species-specific sperm-egg interaction, suggesting the selective pressure is related to male-female interaction. The results provide long-sought evidence for two evolutionary hypotheses: sperm competition and sexual conflict.